Social inclusion, equity, and access in sport participation among marginalized communities: a systematic literature review (2022–2025) - Anisa Sholiha Mia; Ardo Okilanda; M. Arie Desman (Lentera Negeri, 2025)
This study employed a systematic literature review (SLR) following the PRISMA 2020 guidelines. A thematic synthesis approach based on Thomas and Harden (2008) was used to integrate findings across studies. Two independent reviewers performed study screening and quality appraisal using the FICO framework, with disagreements resolved through discussion to ensure methodological consistency. We followed the PRISMA 2020 guidelines. A structured search on Scopus gave us 1, 281 records published between 2022 and 2025. We removed three duplicates and screened the remaining 1, 278 titles and abstracts. That led to 72 full-text articles that we assessed. Ten of those made it into our qualitative synthesis. The included studies represented diverse marginalized populations, including people with disabilities, ethnic minorities, LGBTQ+ individuals, refugees, socioeconomically disadvantaged communities, women, and older adults. We appraised study quality using the FICO framework and analyzed the data through thematic synthesis. Three themes emerged. First, barriers are multidimensional. They span structural, economic, spatial, cultural, and interpersonal factors. Second, the benefits of sport depend on prior inclusion. Sport tends to reflect social integration rather than create it. Third, inclusion policies can unintentionally reinforce inequalities because they often rest on assimilationist ideas. Pulling together perspectives from social inclusion, social capital, intersectionality, capability, and social-ecology, the review highlights the need for equity-focused, intersectional, community-driven approaches. Looking ahead, research should prioritize longitudinal studies, intersectional analyses, work from the Global South, and community-led projects.